Exploring Cross-Modal Influences on the Evaluation of Indoor-Environmental Conditions - Berger, Christiane; Mahdavi, Ardeshir (Frontiers in Built Environment, 2021)
The comfort requirements of occupants influence indoor-environmental factors and energy performance of buildings. Occupants are typically exposed to a multitude of indoor-environmental factors, including a variety of different thermal, auditory, visual, and air quality conditions. However, the bulk of past research and derivative indoor-environmental codes and standards concerning the comfort of occupants address the multiple indoor-environmental stimuli in isolation. Starting from a brief review of past research on multi-perceptual indoor-environmental assessments of occupants, the present study pursues an experimental approach to explore the potential cross-modal effects on the evaluation of indoor-environmental thermal, visual, and acoustic aspects. In this context, a laboratory space including two adjacent identical mock-up office rooms was used to conduct multi-aspect parametric studies with human participants. Different thermal, visual, and auditory conditions were maintained in these two units. In the course of the present study, 296 participants were exposed, on a short-term basis, to different combinations of thermal, visual, and auditory conditions. The experiments were intended to explore if the evaluation of one aspect of the indoor environment could be influenced by differences in the values pertaining to the other aspects. The experimental results are presented and discussed, including their limitations.